A Study on the Multinational Management of Working Capital: The Impact of Multinational Companies on Economic Development (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In the present day world of Globalization, Multinational Companies have played an important role in the development of home countries where the MNCs are operating. Foreign direct investment by multinational companies involves much more than just transfer of capital as it brings with them technologies of production, managerial services and other business practices. Employment opportunities created by the MNCs have solved an important problem of unemployment which is an important characteristic of the underdeveloped as well as developing countries. With the shortage of savings for financing developmental projects, there is need to depend on foreign capital. Inviting and making ways for MNCs to operate in India will enhance the economic development of the country. Prime Minister Narendra Modi’s initiatives for ‘Make in India’ and ‘Skill India’ campaigns, inviting Global Companies to invest in India as well as efforts to simplify the Foreign Direct Investments regulations will certainly make India a favourite destination of MNCs.